Pelatihan Microsoft Office Bagi Guru Paud Di Kota Pematangsiantar Sebagai Upaya Pengembangan Dan Peningkatan Kemampuan Dalam Menggunakan Aplikasi Olah Kata - Agus Perdana Windarto; Anjar Wanto (Jurnal TUNAS, 2020)
The results of the implementation of service activities that have been carried out that PAUD teacher's knowledge about microsoft office learning as an application of word processing is still inadequate prior to the training. This is indicated from the results of the pre-test. Activities carried out by the team of lecturers and students of STIKOM Tunas Bangsa "Pemburu Jurnal" in kindergarten. Nazaret HKBP addressing Jl. Jend. Ahmad Yani No. 63 Pematangsiantar is a positive activity that aims to equip PAUD teachers about technological knowledge, especially microsoft office as a word processing application that is required to be known in technological 4.0. The number of 60 PAUD teacher participants in the city of Pematangsiantar who worked on the pre-test and post-test stated that the insights of knowledge about learning Microsoft Word as an application of word processing increased. In the pre-test session, test participants can answer a maximum of 9 questions correctly by 8% (5 participants) and no one can answer 10 questions correctly (0%). While in the post test session, participants were able to answer all questions correctly as many as 10 questions by 45% (28 participants).